Answer :

**Concept Used:**

(a + b)(a – b) = a^{2} – b^{2}

**Explanation:**

Let a = 100 and b = 6

Then,

106 × 94 = (100 + 6)(100 – 6)

106 × 94 = (100)^{2} – (6)^{2}

106 × 94 = 10000 – 36

**106 × 94 = 9964.**

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Champ Quiz | Polynomials29 mins

Polynomials - Zero to Hero42 mins

Genius Quiz | Polynomials40 mins

Zeros and Degrees of a Polynomial41 mins

Methods to find zeroes of a Polynomial-246 mins

Remainder Theorem and Factor Theorem38 mins

Genius Quiz | Division of Algebraic Expressions37 mins

Introduction to Polynomials37 mins

Basic understanding of Polynomials37 mins

Quiz | Imp. Qs. on Algebraic Identities65 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Factorize:

x^{2}+x+

75×75+2×75×25+25×25 equal to

RD Sharma - MathematicsFactorize:

a^{3}-3a^{2}b+3ab^{2}-b^{3}+8

If x+ =5, then *x*^{2}+=

If *a*^{2}+ =102, find the value of *a*-.

Factorize:

2 – 50x^{2}

Factorize:

100 – 9x^{2}

Factorize:

10x^{2} – 9x – 7

Factorize:

9x^{2} + 16y^{2} + 4z^{2} –24xy + 16yz – 12xz

Factorize:

2x^{2}-x+